Water conflicts related to management of multi-purpose reservoirs in Vu Gia - Thu Bon River Basin - Nguyễn, Thị Nhật Anh (2020)
Water conflict is becoming an urgent problem over the world because of rapid economic development leading to the rapid increase of water demand, and global climate change to the decrease of water availability in season dry. This study is about water conflict occurring in Vu Gia - Thu Bon river basin among three main water users: hydropower reservoirs in upstream as well as an irrigation system and urban water supply in downstream. In order to understand deeply their interactions, this study builds a game theoretical model to describe the current conflict and their benefits in exploiting water. From the general model, the practical model is calculated by secondary data and then is modified with water right weight and average values. The initial results are that although the profitability for the whole agricultural sector is the largest, the average value is negligible. In contrast, the profitability of hydropower and water supply companies is lower but more concentrated. In the perspectives of policymakers, it is essential to analyse the movement of each player, consider the total payoff values and use control variables as “refund” and “punishment” to adjust some water user’s behaviors.